Acid and alkaline phosphatase localization in the digestive tract mucosa of the Hemisorubim platyrhynchos - Faccioli, Claudemir Kuhn [UNESP]; Chedid, Renata Alari [UNESP]; Mori, Ricardo Hideo [UNESP]; Amaral, Antônio Carlos do [UNESP]; Franceschini-Vicentini, Irene Bastos [UNESP]; Vicentini, Carlos Alberto [UNESP] (Elsevier, 2016)
This cytochemical study investigated the acid and alkaline phosphatase of the digestive tract of Hemisorubim platyrhynchos. Acid phosphatase was detected in the lining epithelium throughout the digestive tract, whereas alkaline phosphatase was only observed in the intestine. In the esophagus, an acid phosphatase reaction occurred in the apical cytoplasm of the epithelial cells and was related to epithelial protection and freeing of superficial cells for sloughing. Similar results were also observed in epithelial cells of gastric epithelium. In the gastric glands, acid phosphatase occurred in lysosomes of the oxynticopeptic cells acting in the macromolecule degradation for use as an energy source, whereas in the vesiculotubular system, its presence could be related to secretion processes. Furthermore, acid phosphatase in the intestine occurred in microvilli and lysosomes of the enterocytes and was correlated to absorption and intracellular digestion. However, no difference was reported among the regions of the intestine. However, alkaline phosphatase reaction revealed a large number of reaction dots in the anterior intestine, with the number decreasing toward the posterior intestine. This enzyme has been related to several functions, highlighting its role in the nutrient absorption primarily in the anterior intestine but also being essential in pH regulation because this is a carnivorous species with many gastric glands with secretions that could damage the intestine.
Keywords: Catfish; Cytochemistry; Epithelium; Teleost; Ultrastructure